Epistemologies of the Body : Cultural Resistance in Salvador (Brazil) and Cartagena (Colombia) - Gruber, Valerie (2021)
Salvador da Bahia (Brazil) and Cartagena de Indias (Colombia) are traumatic places where Afro-diasporic communities challenge persistent colonial ideologies through manifold practices of resistance. Both cities were former ports of the transatlantic trade in enslaved Africans and, nowadays, they are recognized as UNESCO World Heritage sites. This paper explores how residents of marginalized neighborhoods in both cities struggle against domination by means of cultural practices such as music, dance and poetry. Their movements, rhythms, song texts and Afro hairstyles contest racialized stigmatization and inscribe counter-narratives in spaces structured by (neo-)colonial hierarchies. They help recover from traumatic experiences, preserve silenced memories, reconstruct fragmented identities and re-signify neglected knowledges. To engage with these bodily modes of cultural resistance, which are often sidelined by Western academia, we developed an approach of participatory action research with the REPROTAI network from Salvador and the Candilé cultural group from Cartagena. Since the beginning of the Covid-19 pandemic, however, we have been realizing our activities only in the virtual sphere. Thereby, the bodily dimension of cultural resistance turned out to be even more important than previously thought. Against this backdrop, my paper explores the notion of Epistemologies of the Body, focusing on those processes of resistance that are ephemeral, tactical and corporeal. This is particularly important in places where black bodies have been systematically objectified and violated for centuries. As a whole, the project aims at calling our attention to collective practices which are often overlooked by linguistic and discursive academic approaches.
Keywords: Epistemologies; Body; Culture; Resistance; African diaspora